Persepsi pekerja terhadap implikasi gangguan seksual di tempat kerja. - Eles, Binti Abang Nen (Universiti Malaysia Sarawak (UNIMAS), 2002)
The purpose of this research is to identify workers awareness about sexual harassment and their perception toward its implication that exist in the workplace at Percetakan Nasional Malaysia Berhad (PNMB) of Sara wak branch. This study is based on demographic criteria that consists gender, marital status, age, race, work period and also position. Questionnaires were used to gain a feedback from respondents. By using simple random sampling, the respondent consists of 45 workers of various groups in PNMB. The collected data were analyzed using Statistical Package ofScience Social Version (SPSS) versionJO.O. One-way ANOVA and t-test indicated that there are no significant differences between all of the selected demographical factors. Overall findings show that majority of workers aware about sexual harassment issues that exist in the workplace. They agree that sexual harassment give impact to workers emotion, behavior, and peer relationship. For that reason, organization has to introduce a various policy and program to avoid sexual harassment problem at the workplace.